The Role of Demography, Geographical Constraints, and Land Regulations on House Price in Malaysia - Saizal Pinjaman; Sarma Aralas; Debbra Toria Nipo (Macrothink Institute, 2022)
The current paper investigates the influence of demography, geographical constraints, and land regulation on house price in Malaysia based on the developers’ perspective. A survey questionnaire was distributed among the real estate developers in the country and for the demographical factors, population growth, income, standard of living, and household confidence on future prices are identified to be important determinants. Meanwhile, in terms of land regulations, a majority of the developers believed that the cost of land acquisition, zoning regulations, and land statuses are important on house price setting. Apart from that, geographical constraints including land reclamation, forest clearing, and hillslope stripping are also considered by the developers. In ensuring that the house price remains affordable, land regulations on real estate development should be more relaxed to stimulate housing projects at lower costs. In addition, price speculation should also be monitored if not curbed so that the house price remains affordable particularly for the medium and low-income earners.